Racism Toward Chinese Ethnic Group in Indonesian Social Media: Hate Speeches Analysis from Forensic Linguistic Perspective - Astri Dwi Floranti (Universitas Pasundan, 2022)
Anti-Chinese sentiments are still deeply ingrained in the Indonesian public discourse. The issue of their identity and position is debatable that triggers to many discriminatory actions toward them. The purpose of this study is to analyze hate speech against Tionghoa ethnic expressed in Indonesian social media which has officially evaluated as a legal offense by the authorities. The theory of speech acts from Austin (1962) and Searle (1969) within forensic linguistic study are employed to examine the utterances and evaluate them in the context of Indonesian legal regulations. The data was obtained from Direktori Putusan Mahkamah Agungfrom 2019 - 2021. The results of the analysis reveal that hate speech portrays hurtful feelings and harmful attitudes. It is reflected by malice (expressive speech act), insulting or accusing (assertive speech act), persuading the others to commit crimes (directive speech act), planning crimes in the future time (commissive speech act). Then, there are 10 forms of pejorative labels toward Tionghoa ethnic. Race-based hate speeches expressed in the online media are prohibited in Article 28 paragraph (2) of The ITE Law Article Number 19 of 2016. They are prejudiced action, violate human rights and cannot be considered as freedom of opinion and democracy because of their dangerous perlocutionary effects. The effects can provoke discriminatory action and even crime.